2005
DOI: 10.1002/cncr.21593
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of high‐dose chemotherapy before radiation in children with newly diagnosed high‐grade astrocytoma

Abstract: BACKGROUND High‐grade astrocytomas (HGA) carry a dismal prognosis and compose nearly 20% of all childhood brain tumors. The role of high‐dose chemotherapy (HDCT) in the treatment of HGA remains unclear. METHODS In a nationwide study, The Children's Cancer Group (CCG) prospectively evaluated 102 children with HGA and postoperative residual disease for efficacy and toxicity of four courses of HDCT before radiotherapy (RT). Patients were randomly assigned to one of three couplets of drugs: carboplatin/etoposide (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 29 publications
(30 reference statements)
5
29
0
2
Order By: Relevance
“…Unfortunately, none of the three treatment arms showed beneficial effect toward survival. 90 The SFOP treated high-grade glioma patients with limited success with a combination of carmustine, cisplatin, and etoposide after surgery. The 5-and 10-year OS were reported at 16% (Ϯ 9%) and 13.3% (Ϯ 9.4%), respectively.…”
Section: Chemotherapymentioning
confidence: 99%
“…Unfortunately, none of the three treatment arms showed beneficial effect toward survival. 90 The SFOP treated high-grade glioma patients with limited success with a combination of carmustine, cisplatin, and etoposide after surgery. The 5-and 10-year OS were reported at 16% (Ϯ 9%) and 13.3% (Ϯ 9.4%), respectively.…”
Section: Chemotherapymentioning
confidence: 99%
“…However toxic adverse effects are frequently reported (18). Central nervous system-directed treatment using intraventricular drug injection is one approach to overcoming the blood-brain barrier protective effect against anticancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although subsequent studies have all utilized chemotherapy, further improvements in outcome have not been realized. [10][11][12][13] With the advent of temozolomide, there was renewed hope that outcome could be improved. The benefit of temozolomide for adults with newly diagnosed HGGs was established in a randomized study by Stupp et al,4 who showed a significant improvement in OS and PFS in newly diagnosed adults with glioblastomas treated with temozolomide during and after RT compared to those treated with RT alone.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,18 The Children's Cancer Group 9933 (CCG-9933) study evaluated the combinations of "high-dose" carboplatin/VP-16, cyclophosphamide/ VP-16, and ifosfamide/VP-16 prior to RT. 11 More than half of the patients either progressed during chemotherapy or did not complete chemotherapy because of toxicity, and 21% of the patients never received RT. In contrast, the combination of lomustine/temozolomide at the MTD was generally well tolerated, and only one patient ment without a change in tumor-specific treatment is becoming increasingly recognized.…”
mentioning
confidence: 99%